(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Deep Learning is a branch of Machine Learning (ML) that is used to solve complex problems and come up with intelligent solutions. Artificial Neural Networks (ANN) are used in deep learning to analyze data and make predictions. In the health sector, deep learning has made it possible to use computer aided technology to predict and diagnose the disease. In this paper , we present a comprehensive review on deep learning algorithms and how it is used in healthcare to predict and diagnose various diseases.